Receptor-Interacting Protein Kinase-2 Inhibition by CYLD Impairs Antibacterial Immune Responses in Macrophages - Wex, Katharina; Schmid, Ursula; Just, Sissy; Wang, Xu; Wurm, Rebecca; Naumann, Michael; Schlüter, Dirk; Nishanth, Gopala (Frontiers in Immunology, 2016)
Upon infection with intracellular bacteria, nucleotide oligomerization domain protein 2 (NOD2) recognizes bacterial muramyl dipeptide and binds, subsequently, to receptor-interacting serine/threonine kinase 2 (RIPK2). RIPK2 mediates the activation of immune responses via the nuclear factor-κB (NF-κB) and extracellular-signal regulated kinase (ERK) pathways. Previously, it has been shown that RIPK2 activation dependens on its K63-ubiquitination by the E3 ligases pellino-3 and ITCH, whereas the deubiquitinating enzyme A20 counter-regulates RIPK2 activity by cleaving K63-polyubiquitin chains from RIPK2. Here, we newly identify the deubiquitinating enzyme CYLD as a new interacting partner and inhibitor of RIPK2. We show that CYLD binds to and removes K63-polyubiquitin chains from RIPK2 in Listeria monocytogenes (Lm) infected bone-marrow-derived macrophages (BMDM). CYLD-mediated K63-deubiquitination of RIPK2 resulted in an impaired activation of both NF-κB and ERK1/2 pathways, reduced production of proinflammatory cytokines (IL-6, IL-12), anti-listerial ROS and NO, and, finally, impaired pathogen control. In turn, RIPK2 inhibition by siRNA prevented activation of NF-κB and ERK1/2 and completely abolished the protective effect of CYLD-deficiency with respect to the production of IL-6, NO, ROS and pathogen control. Noteworthy, CYLD also inhibited autophagy of Listeria in a RIPK2-ERK1/2 dependent manner.The protective function of CYLD-deficiency was dependent on IFN-γ pre-stimulation of infected macrophages. Interestingly, the reduced NF-κB activation in CYLD-expressing macrophages limited the protective effect of IFN-γ by reducing NF-κB-dependent STAT1 activation. Taken together, our study identifies CYLD as an important inhibitor of RIPK2-dependent anti-bacterial immune responses in macrophages.